CRITICAL ANALYSIS OFAFGHAN WOMEN IN KHALED HOSSEINI’S NOVELA THOUSAND SPLENDID SUNS (International Journal of Food and Nutritional Sciences, 2022)
This paper deals with the problems of Afghan women through the characters of the novel A Thousand Splendid Suns. Khaled Hossini, a well-known American author of Afghan descent, who wrote this novel. The characters in his novels do the finest job of illuminating the place of women in Afghan culture. In A Thousand Splendid Suns, there are numerous instances where these ladies are forced to make judgements. Women are required to abide by rigid social norms that specify how they should behave around all men in the community.In Afghan society, a woman is expected to uphold moral principles and follow accepted social norms. In Afghan culture, a woman must support her husband’s family and carry out the expectations of a wife. In Afghan society, cultural norms that portray women as less capable than their male counterparts determine a woman’s place in society. Women must be managed and protected because they stand for the dignity of the family, community, and country, in order to preserve their moral purity.They aren’t allowed to look up at or establish eye contact with men. They might never interact with males in person. Women should wear modest clothing that covers any exposed skin. It is forbidden to laugh aloud. Afghan women have historically been denied many of their legal rights and their lives have been restricted by the veil, despite the fact that Islam dictates that men and women be treated equally before the law.